Fault Distance Identification Using Impedance and Matching Approaches on Distribution Network - Lilik Jamilatul Awalin; H. Mokhlis; M. K. Rahmat; Sophi Shilpa; Fadi Albatsh; Bazilah Ismail (Institute of Advanced Engineering and Science, 2017)
In this paper, impedance based method and matching approaches were used separately to detect three phase to ground fault (LLLGF). In order to observe the accuracy of each method, Non-homogeneous distribution network was used as a tested network. Actual data from TNB (Tenaga National Berhad) Malaysia was adopted to model the network by using PSCAD/EMTDC simulation program. Both methods were tested to observe the accuracy of fault distance estimation. The comparison result shows different accuracy for each section which simulated in the middle of section. Based on the complexity of the distribution network, it possible to contribute difficulty to obtain the maximum accuracy. The result was obtained through the complete process which involves the database formation acquired through the PSCAD/EMTDC software simulator and the fault location distance calculation carried out by the MATLAB software.